Fracture of notched ductile bulk metallic glass bars subjected to tension-torsion : experiments and simulations - Raut, Devaraj (2021)
In bulk metallic glasses (BMGs) that are susceptible to shear band mediated plasticity, crack initiation and growth is a strain-controlled process associated with a unique material specific length scale. In notched specimens subjected to pure modes I and II, and mixed mode I/II loading conditions, this length scale determines the extent to which a crack can grow within a dominant shear band before propagating catastrophically. While a similar fracture mechanism is expected in the anti-plane shear mode (mode III) dominant loading condition, there are few studies that have investigated this aspect. In this paper, an attempt is made to understand the crack growth processes and fracture mechanisms under mode III and mixed mode I/III loading conditions by conducting pure torsion and combined tension-torsion experiments on a Zr-based BMG that exhibits significant room temperature plasticity. Specimens with either high or low notch acuity are tested to assess the effects of plastic constraint on the fracture process. Detailed finite element simulations were performed to study the evolution of stress and strain fields within each specimen before the onset of fracture. These are correlated with the fractographic features to determine the fracture criterion and mechanism. Results indicate that the length scale associated with fracture and the mechanism of crack growth are both sensitive to the application of tensile loads. The fracture toughness of BMGs under different modes of loading are evaluated and compared.